The Canadian alcopop tragedy should trigger evidence‐informed revisions of federal alcohol regulations. (4th February 2019) - Paradis, Catherine; April, Nicole; Cyr, Claude; Morin, Réal; Niquette, Manon
Abstract: On 1 March 2018, a 14‐year‐old girl was found lifeless in a stream behind her high school after having consumed FCKDUP—a beverage containing 11.9% alcohol and sold in 568 mL cans—during her lunch hour. Following her death, the Canadian government took actions at ministerial and parliamentary levels by seeking experts' advice to better regulate highly sweetened alcoholic beverages, otherwise referred to as 'alcopops'. We suggest that the Canadian government uses the work surrounding the alcopop tragedy as an opportunity to make significant amendments and revisions of federal alcohol regulations.